(untitled) (The Pakistan Development Review, 1995)
Improving the material conditions of the poor has been the main focus of economic policy formulation for the past fifty years or so. Thus, in this connection, a vast body of literature has been published which deals with such issues as identifying the poor and suggesting remedies to alleviate their lot. The book by Theodore W. Schultz deals specifically with the economics of the poor. The book is primarily a collection of articles the author wrote over a fortyyear period (1950-1990), and these have been published previously in a number of leading economic journals. The articles have been grouped under three headings: "Most People Are Poor"; "Investing in Skills and Knowledge"; and "Effects of Human Capital". The articles basically deal with the concept of human capital. There is a logical sequence to the articles that make up this book; the poor are identified and steps are then suggested to improve their standing. Issues such as women’s economic emancipation and the demand for children are highlighted in the collection of articles dealing with these two subjects. By investing in themselves through education, the poor raise their level of skills, and thus their level of wages/salaries, allowing them to enjoy higher standards of living.